Protective Role of the MER Tyrosine Kinase via Efferocytosis in Rheumatoid Arthritis Models - Waterborg, Claire E. J.; Beermann, Silke; Broeren, Mathijs G. A.; Bennink, Miranda B.; Koenders, Marije I.; van Lent, Peter L. E. M.; van den Berg, Wim B.; van der Kraan, Peter M.; van de Loo, Fons A. J. (Frontiers in Immunology, 2018)
Abstract Objective: Rheumatoid arthritis is a chronic and progressive joint disease. It appears that anti-inflammatory feedback mechanisms that could restrain joint inflammation and restore homeostasis are insufficient to perform this control. In this study, we investigated the contribution of the MER tyrosine kinase-mediated anti-inflammatory response on arthritis and whether targeting MER could be a valid approach to treat RA. Methods: KRN serum transfer arthritis (KRN STA) was induced in either Mertk-deficient mice, or in mice that adenovirally overexpressed Pros1. Human synovial micromasses were treated with MER-specific antibodies or PROS1. Collagen-induced arthritis (CIA) mice were treated with MER-specific agonistic antibodies or by viral overexpression of Pros1. Results: Mertk-/- mice showed exacerbated arthritis pathology whereas Pros1 overexpression diminished joint pathology in KRN STA. Human synovial micromasses challenged with MER-specific antibodies enhanced the secretion of inflammatory cytokines whereas stimulating MER with PROS1 reduced the secretion of these cytokines, confirming the protective role of MER. Next, we treated CIA mice with MER-specific agonistic antibodies and this unexpectedly resulted in exacerbated arthritis pathology. This was associated with increased numbers of apoptotic cells in their knee joints and higher serum levels of IL-16C, a cytokine released by secondary necrotic neutrophils. Apoptotic cell numbers and IL-16C levels were enhanced during arthritis in Mertk-/- mice and reduced in Pros1-overexpressing mice. Conclusion: MER plays a protective role during joint inflammation and activating MER by its ligand PROS1 ameliorates disease. Treatment of mice with MER receptor agonistic antibodies is deleterious due to its counterproductive effect of blocking efferocytosis in the arthritic joint.